Evaluation of the 2-D permeability tensor for fractured rock masses - Zhang, X.; Sanderson, D.J.; Harkness, R.M.; Last, N.C. (International journal of rock mechanics and mining sciences & geomechanics abstracts, 1996)
An approach is established to evaluate the 2-D permeability tensor of naturally fractured rock masses by using modified UDEC ¶. Based on the superposition principle, directional flow-rates through a unit square of fractured rock under head gradients in two orthogonal directions can be calculated with UDEC. Then the flow-rates are transformed into flow-rates through a field rock mass for evaluating the permeability tensor. Two kinds of fractured rock models, fixed hydraulic fracture aperture and variable hydraulic fracture aperture under stress, were studied by using this approach. For the first model, the permeability tensor of a fractured rock mass only depends upon the statistical features of fracture pattern geometry, including orientation, trace length, density of fractures. For the second model, the permeability tensor strongly depends upon both the geometry of the fracture pattern and the applied stress, such as the direction and magnitude of principal stress as well as the ratio of major principal stress to minor principal stress.